IMPLEMENTASI PENYEDIAAN INFORMASI PUBLIK DI BIRO HUMAS DAN PROTOKOL SEKRETARIAT DAERAH PROVINSI KALIMANTAN BARAT - MELVINA, MELVINA; Triyono, Joko; Ningtias, Kartika (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This research aimed to describe and analyze the factors that caused the implementation of public information provision in the Documentation Section at the Bureau of Public Relations and Protocol of Regional Secretariat of West Kalimantan Province.  The method used in this research was qualitative with exploratory analysis research design. This research used the theory of George C. Edward III (in Agustino, 2014,149), namely: 1) Communication, it was concluded that the implementation of public information provision to the public had been given or delivered properly 2) Resources, it was concluded that employees in the Bureau of Public Relations and Protocol,  especially in the documentation section, were still very lacking and many were retiring. The delivery of public information to employees and the public had gone well, but facilities and infrastructure were still lacking. 3) Disposition, the conclusion was that the implementation of public information provision was decent, there were no incentives in the Bureau of Public Relations and Protocol, indicating the lack of a source of encouragement in carrying out the implementation such as incentives in the form of adequate work fees to employees at the Bureau of Public Relations and Protocol of Regional Secretariat of West Kalimantan Province  and 4) Bureaucratic Structure, the conclusion was that the standard operating procedure protocol in public information provision at the Bureau of Public Relations and Protocol of the Regional Secretariat of West Kalimantan Province had been running well. Keywords: Implementation, Public Information Provision.